Data Analysis of Student Attitude Survey Based on Internet Analysis Technology - Cao, Yongcheng; Liu, Quanguo; Chen, Huajie (Journal of Applied Data Sciences, 2022)
Language attitude is people’s understanding and evaluation of languages, which has important effect on language learning. Based upon investigation into 605 tibetan college students from 5 colleges in Tibet areas, and combined with network data, this paper mainly analyses their attitude towards Tibetan, Chinese and English from four dimensions: recognizing, instrumental, integrative and transferring attitude. This paper also discusses the relationship between students’ language attitude and their gender and grade.